Genetic analysis of candidate modifier polymorphisms in Hb E-β0-thalassemia patients - Orapan Sripichai (2018)
Hemoglobin E (Hb E)-β-thalassemia patients display a range of clinical severities, from nearly asymptomatic to transfusion-dependent: thalassemia major. Given this clinical heterogeneity, additional genetic factors modifying disease severity remain to be discovered. Association studies are being conducted to elucidate the role of genetic polymorphisms as disease severity modifiers in Hb E-β-thalassemia patients. Using strict scoring criteria, 1060 Hb E-β-thalassemia patients were categorized into mild, moderate, and severe groups. Taking a candidate gene approach, we found no statistically significant differences between the mild and severe patients groups in allelic or genotypic frequencies for single nucleotide polymorphisms within five genes known to influence globin gene expression and erythropolesis. © 2005 New York Academy of Sciences.